Transforming multilateral diplomacy the inside story of the sustainable development goals - Kamau, Macharia; Chasek, Pamela S. 1961-; O'Connor, David (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2018)
"Transforming Multilateral Diplomacy provides the inside view of the negotiations that produced the UN Sustainable Development Goals (SDGs). Not only did this process mark a sea change in how the UN conducts multilateral diplomacy, it changed the way the UN does its business. This book tells the story of the people, issues, negotiations, and paradigm shifts that unfolded through the Open Working Group (OWG) on SDGs and the subsequent negotiations on the 2030 Sustainable Development Agenda, from the unique point of view of Ambassador Macharia Kamau, and other key participants from governments, the UN Secretariat, and civil society."--Provided by publisher